Definition of police psychology: The role of psychologist in the police - Alispahić, Bakir; Alispahić, Sabina (Technium Social Sciences Journal, 2021)
Police psychology is a sub discipline of forensic psychology. By definition, police psychology is ‘the research and application of psychological principles and clinical skills for law enforcement and public safety’. The basic tasks of a police psychologist are evaluation, conducting training and coaching of police officers, assisting in organizational development and providing psychological services. The practice of calling a psychologist to the police service only when necessary should be changed because in that way not all the benefits of a wide range of talents and skills that a psychologist can provide to the police can be obtained. Police psychology offers much more than individual interventions. Despite the evident interest in this area of ??psychology, in our region it is still not clear enough what police psychology is and what is the role of psychologists in the police. Therefore, the aim of this paper is to try to define the field of police psychology through a detailed description of the role of psychologists in the police forces.